Rhoticity in Chinese English: An experimental investigation on the realization of the variant (r) in an Expanding Circle variety - Li, Zeyu; Kabak, Barış (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2017)
The realization of postvocalic /r/ has been frequently examined in both diachronic and synchronic research on world Englishes, showing a multitude of linguistic and extra-linguistic factors to modulate the degree of rhoticity. Since rhoticity is one of the most important indices of variation across Englishes, it forms an instructive phonological marker to investigate the dynamics of norm formation in emerging varieties. While the Inner and Outer Circle varieties have been extensively studied, there is fairly little research on the variable realization of postvocalic /r/ in the Expanding Circle Englishes. Here, we fill this gap with a study on the degree of rhoticity by highly proficient users of an EFL variety emerging in China, college English teachers, who are pertinent norm providers for EFL learners. We provide a multivariate analysis of phonological and sociolinguistic factors conditioning the degree of rhoticity in Chinese English on the basis of speech production data from 13 participants. Results show that Chinese English is best categorized as marginally rhotic. Concerning the patterning of phonological variables, it aligns more with Inner Circle than Outer Circle Englishes, albeit with significant inter- and intra-speaker variability. We discuss the competing roles of norm orientation, substrate influence, and other relevant variables therein.